EFFECT OF SUBLETHAL DOSE OF PENICILLIC ACID TOXICITY ON GROWTH, IMMUNITY AND LYMPHOID ORGANS IN BROILER CHICKENS: Pharmaceutical Science-Pathology - N. PAZHANIVEL; C. BALACHANDRAN; MANOHAR, B.MURALI; G.DHINAKARRAJ; V.BALAKRISHNAN; KIRUBAHARAN, J.JOHN (International Journal of Life Science and Pharma Research, 2014)
Penicillic acid (PA), a mycotoxin, was originally isolated from the cultures of Penicillium puberulum. The present study was undertaken to find out the sublethal effect of penicillic acid mycotoxicosis on growth rate and immune status of broiler chicken. Forty eight day-old broiler chicks were randomly allotted to four groups of 12 birds each and fed with 0, 7.5, 15 and 30 ppm of penicillic acid from 0 to 21 days of age respectively. Two birds from each group were sacrificed on 7th, 14th and 21st day of age to study the cell mediated immunity (CMI) of birds. On 21st day of trial, remaining birds were sacrificed to study the pathological changes in lymphoid organs and immune status. There were highly significant reduction (P<0.01) in the body weight gain of broiler chicken at 15 and 30 ppm levels. Highly significant reduction (P<0.01) in the NDV antibody titres were observed in the 7.5 and 15 ppm penicillic acid fed birds. Highly significant decrease (P<0.01) in the splenocyte stimulation index value was found in the 30 ppm group when compared to the control and other groups. Microscopically, Bursa of Fabricius showed hyperplastic lining epithelium with multiple cystic changes in the 7.5 ppm group. Splenic reticulum cell hyperplasia, cystic changes in the bursa of Fabricius, starry-sky appearance in the thymus, mild lymphoid depletion in the caecal tonsils and mild plasma cell depletion in the Harderian gland were also observed in 15 ppm group. This research indicated that the PA toxin caused a reduction in growth rate at 15 in broiler chicken and immune suppression even at sublethal dose of 7.5 ppm.